2018 30th International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD) 2018
DOI: 10.1109/cahpc.2018.8645906
|View full text |Cite
|
Sign up to set email alerts
|

On the Resilience of RTL NN Accelerators: Fault Characterization and Mitigation

Abstract: Machine Learning (ML) is making a strong resurgence in tune with the massive generation of unstructured data which in turn requires massive computational resources. Due to the inherently compute-and power-intensive structure of Neural Networks (NNs), hardware accelerators emerge as a promising solution. However, with technology node scaling below 10nm, hardware accelerators become more susceptible to faults, which in turn can impact the NN accuracy. In this paper, we study the resilience aspects of Register-Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…• 2 We observed that various layers of the given NN have different inherent vulnerability to faults. We conducted a pre-processing analysis and observed that inner layers (layers closer to the output) are relatively more vulnerable, as similarly observed in [31], [32], [33], since faults in these layers have relatively less probability to be masked through the quantification in the activation functions. The sensitivity of NN layers, i.e., {Layer j , j ∈ [0, 4]} is evaluated by injecting simulated randomlygenerated faults in corresponding weights of individual layers at the Register-Transfer Level (RTL).…”
Section: Fault Mitigation Techniquementioning
confidence: 70%
See 1 more Smart Citation
“…• 2 We observed that various layers of the given NN have different inherent vulnerability to faults. We conducted a pre-processing analysis and observed that inner layers (layers closer to the output) are relatively more vulnerable, as similarly observed in [31], [32], [33], since faults in these layers have relatively less probability to be masked through the quantification in the activation functions. The sensitivity of NN layers, i.e., {Layer j , j ∈ [0, 4]} is evaluated by injecting simulated randomlygenerated faults in corresponding weights of individual layers at the Register-Transfer Level (RTL).…”
Section: Fault Mitigation Techniquementioning
confidence: 70%
“…Ares [61] is a framework for quantifying the resilience of deep neural networks. Also, [31] studied an RTL model of the NN from resilience perspective by injecting faults in the registers of the design. Also, recently [33] studied the fault propagation in an ASIC model of NN focused on the vulnerability of different NN layers.…”
Section: B Recent Related Studies On Nnsmentioning
confidence: 99%
“…Hence, recently, the resilience of DNNs has been studied in different abstraction levels. A vast majority of the previous works in this area belong to the DNN inference phase, including simulationbased efforts [33]- [36] and works on the real hardware [12], [37]- [39]. The verification of the simulation-based works on the real fabric can be a crucial concern; also, the real hardware works are mostly performed on the customized ASICs, which of course, reproducing those results on the COTS systems is a crucial question.…”
Section: Related Workmentioning
confidence: 99%
“…ThUnderVolt [178] proposes to underscale the voltage of arithmetic elements. Salami et al [141] and Zhang et al [179] present fault-mitigation techniques for neural networks that minimize errors in faulty registers and logic blocks with pruning and retraining.…”
Section: Related Workmentioning
confidence: 99%
“…Sixth, works that study the intrinsic error resilience of DNNs by injecting randomly-distributed errors in DNN data [110,110,141,163,166,179,180]. These works assume that the errors can come from any component of the system (i.e., they do not target a specific approximate hardware component).…”
Section: Related Workmentioning
confidence: 99%